Digital Transformation for Protected Forest Governance: A Policy Reform Framework for Land-Use Licensing in Indonesia - Didi Nursidi (Sultan Publisher, 2025)
Digital transformation has increasingly been discussed as a potential driver of reform in natural resource governance, particularly in the management of protected forests through land-use permitting systems. In practice, however, the digitalization of licensing processes has largely emphasized administrative efficiency and procedural simplification, while its function as a legally institutionalized instrument of environmental control remains limited. This study examines the regulatory and institutional configuration of land-use permitting in protected forest areas in Indonesia and develops a policy reform framework that positions digital transformation within governance and legal reform. Employing a normative legal approach combined with qualitative policy analysis, the research reviews statutory frameworks, institutional arrangements, and policy documents related to forestry regulation, spatial planning, and digital licensing systems. The analysis indicates that protected forest governance continues to face regulatory fragmentation, overlapping institutional mandates, limited spatial data integration, and accountability constraints within existing digital licensing structures. In response, the study formulates a sector-specific reform framework structured around four interconnected pillars: regulatory harmonization, institutional integration and accountability, integrated digital licensing architecture, and environmental justice and public participation. Rather than proposing a demonstrated policy outcome, the framework provides a normative and institutional proposition for embedding digital transformation within preventive (ex ante) environmental control and legally coherent governance structures. The results reinforce the conceptual development of digital governance reform in protected forest management while outlining directions for future empirical and socio-legal research.